Petrography, geochemistry and tectonic setting of ‎Hanar granitoids (south of Birjand): a signature for magmatism ‎identification of east of Lut block - Siavash Omidianfar; Mohammad Rahgoshay; Iman Monsef (پترولوژی, 2018)
The Hanar granitoids, geographically located 155 km south of Birjand in the east of Iran. Geologically, It belongs to the Lut block volcanic–plutonic belt and occurs near to the Lut block-Sistan suture zone border. The granitoid rocks consist of tonalite, granodiorite, quartz-diorite, diorite and microdiorite. The predominant textures are granular, porphyritic and myrmekitic. Geochemical evidence reveals that they are co-genetic and have features typical of calk-alkaline to high-K calk-alkaline, metaluminous with I-type nature. Enrichment in LILE (i.e. Cs, K, Rb, U and Th) rather than HFSE (eg., Nb, P, Zr and Ti), typical negative anomalies of Nb and Ti and LREE enrichment in comparison to HREE, are important characteristics indicating that these rocks were formed in a magmatic belt in a subduction zone. Positive anomalies of Pb and K demonstrate the involvement of continental crust in evolution of parental magma. Trace element ratios and adakitic discrimination diagrams point to the non adakitic nature of the magma. Tectonic discrimination diagrams show formation of these rocks in an immature continental arc setting with less than 45 Km crustal thickness in pre-plate collision event. Primitive magmas should have formed by low degree melting (less than 8%) of an eneriched mantle wedge peridotite (spinel lherzolite). During magma ascent, fractional crystallization and crustal contamination (AFC) took place simultaneously. Field observation and petrography studies support this hypothesis.